Kualitas air minum depot isi ulang di Banyumas - Harry Abriandy; Dibyo Pramono; Susi Iravati (Berita Kedokteran Masyarakat (BKM), 2017)
Drinking water quality of refill depots in BanyumasPurposeThis study was conducted to determine the association between water source, reservoir quality, environmental hygiene, hygiene behavioral handlers, filter size, filter quality, the use of disinfectants and the use of a coagulant with the microbiological quality of drinking water refill.MethodsThis analytic observational study used a cross-sectional design. The study population was drinking water depots that have implemented internal monitoring of drinking water quality, the selection of the sample using simple random sampling method, with the total sample of 162.ResultsA total of 140 DWD (86.42%) are eligible microbiological, 22 DWD (13.58%) are not eligible. The source of water that is the most widely used are water wells (53.09%), while the source of water from the taps and springs are used as much as 33.95% and 12.96%, respectively.ConclusionThere is no relationship between the water source, reservoir quality, environmental hygiene, hygiene behavioral handlers, the size of the filter, the use of disinfectants and the use of a coagulant with the microbiological quality of drinking water refill. There is a relationship between the quality of the filter with the microbiological quality of drinking water refill (p-value=0.0304 95%CI 1.006-10.525; PR=3.255).